2016
DOI: 10.1038/bjc.2016.351
|View full text |Cite
|
Sign up to set email alerts
|

Projected cancer risks potentially related to past, current, and future practices in paediatric CT in the United Kingdom, 1990–2020

Abstract: Background:To project risks of developing cancer and the number of cases potentially induced by past, current, and future computed tomography (CT) scans performed in the United Kingdom in individuals aged <20 years.Methods:Organ doses were estimated from surveys of individual scan parameters and CT protocols used in the United Kingdom. Frequencies of scans were estimated from the NHS Diagnostic Imaging Dataset. Excess lifetime risks (ELRs) of radiation-related cancer were calculated as cumulative lifetime risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
0
31
0
2
Order By: Relevance
“…Results of several investigations have suggested the potential benefits of reducing radiation dose for prevention of possible future carcinogenesis attributable to CT. Miglioretti et al (5) demonstrated that reducing the highest 25% of doses of pediatric CT to the median level might prevent 43% of future CT-induced cancers. Journy et al (26) estimated that when the dose per CT scan was reduced by 20% and 40%, respectively, compared with past practices in the United Kingdom, the number of future cancers potentially induced at pediatric CT was reduced by 20% and 40%. The actual benefit of CT dose reduction remains unclear, because estimations are based on risk projection models.…”
Section: Benefits Of Radiation Dose Reduction At Pediatric Ctmentioning
confidence: 99%
“…Results of several investigations have suggested the potential benefits of reducing radiation dose for prevention of possible future carcinogenesis attributable to CT. Miglioretti et al (5) demonstrated that reducing the highest 25% of doses of pediatric CT to the median level might prevent 43% of future CT-induced cancers. Journy et al (26) estimated that when the dose per CT scan was reduced by 20% and 40%, respectively, compared with past practices in the United Kingdom, the number of future cancers potentially induced at pediatric CT was reduced by 20% and 40%. The actual benefit of CT dose reduction remains unclear, because estimations are based on risk projection models.…”
Section: Benefits Of Radiation Dose Reduction At Pediatric Ctmentioning
confidence: 99%
“…In our model, we assigned values (or utilities) to health outcomes using a standard Health Utilities Index scale ranging from 0 (death) to 1 (baseline health, assumed as perfect health for this hypothetical population). The Health Utilities Index is a 15-item questionnaire designed to ask the minimum number of questions required to classify a subject's 10%-50% Sensitivity of CT 32 -37 66% 53%-88% Specificity of CT 32 -37 87% 76%-96% Sensitivity of fsMRI 32,36,38 58% 51%-78% Specificity of fsMRI 32,36,38 93% 89%-98% Sensitivity of ONSD 16 -19 75% 61%-83% Specificity of ONSD 16 -19 32% 22%-38% Sensitivity of SS 33 -35, 37 19% 4%-30% Specificity of SS 33 -35, 37 95% 91%-98% Probability of death and/or missed diagnosis a 0.1% (1:1000) 0.01%-0.2% Probability of radiation-induced malignancy 9,11,21,31,39 0.22% 0.07%-0.6%…”
Section: Utilitiesmentioning
confidence: 99%
“…Incremental HRCT with significant gaps lowers the dose but also diagnostic performance and leads to more motion artifact in the pediatric population [141]. Estimated risk of radiation-induced cancer from a pediatric chest CT is small but not negligible, particularly in cases of repeated exposure [142,143]. MRI has no side effects by radiation enabling long-term surveillance of lung damage.…”
Section: Imaging Characteristics Of Bronchiectasismentioning
confidence: 99%